2021
DOI: 10.1101/2021.07.01.450732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-density transposon mutagenesis in Mycobacterium abscessus identifies an essential penicillin-binding lipo-protein (PBP-lipo) involved in septal peptidoglycan synthesis and antibiotic sensitivity

Abstract: Mycobacterium abscessus (Mab) is a rapidly growing non-tuberculous mycobacterium (NTM) that causes a wide range of infections. Treatment of Mab infections is difficult because the bacterium is intrinsically resistant to many classes of antibiotics. Developing new and effective treatments against Mab requires a better understanding of the unique vulnerabilities that can be targeted for future drug development. To achieve this, we identified essential genes in Mab by conducting transposon-sequencing (TnSeq) on t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
0
0
Order By: Relevance
“…Conversely, genes classified as ‘growth advantage’ cause a fitness benefit relative to wildtype when they are disrupted, resulting in increased insertion counts. The essential genes of the reference strain, ATCC 19977 have been previously reported (25, 27). We compared our predicted essential or growth-defect genes for ATCC 19977 to those in Rifat et al (25), and found an overlap of 393 genes, showing high concordance between these two studies of Mab essentials (Supplemental Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, genes classified as ‘growth advantage’ cause a fitness benefit relative to wildtype when they are disrupted, resulting in increased insertion counts. The essential genes of the reference strain, ATCC 19977 have been previously reported (25, 27). We compared our predicted essential or growth-defect genes for ATCC 19977 to those in Rifat et al (25), and found an overlap of 393 genes, showing high concordance between these two studies of Mab essentials (Supplemental Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Whole Genome Sequencing of Mab Clinical Isolates: Genomic DNA from late-log phase cultures were extracted via a bead-beating and phenol-chloroform protocol described in Akusobi et al (27), using an Illumina Rapid HiSeq 2500 instrument with 125+125 bp paired-end reads.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations